Debt Covenant, Capital Intensity, and Accounting Prudence: Moderating Role of Litigation Risk - Nuryatun; Murwaningsari, Etty; Abdullah, Azrul (Moestopo International Review on Social, Humanities, and Sciences, 2026)
Purpose of research is to analyze (1) effect of debt covenants also capital intensity on accounting prudence. (2) Whether litigation risk moderates effect of debt covenants also capital intensity on accounting prudence. Conducted using secondary data, specifically quantitative data obtained from financial statements of non-financial consumer goods sector companies listed on BEI during period 2023-2024, resulting in a total sample of 210 observations using multiple linear regression analysis. Results of research indicate debt covenants also capital intensity have significant on accounting prudence. Litigation risk was found to moderate relationship between debt covenants also accounting prudence, suggesting that higher litigation risk encourages implementation of more cautious accounting practices. Company size also growth opportunities are used to control company characteristics that influence financial reporting behavior. Empirical results in form of factors that affect accounting conservatism within framework of agency theory also positive accounting theory. This moderation falls under type of Pseudo Moderator Variable, which is a variable that mediates relationship between dependent also independent variables. Litigation Risk cannot significantly moderate relationship between Capital Intensity also Accounting Conservatism.